Desarrollo del lenguaje y su impacto en la lecto-escritura en los niños de inicial 1 de la Unidad Educativa Carlos Coello Icaza - Alarcón Naranjo, Silema (2023)
The present case study was carried out in the Carlos Coello Icaza Educational Unit of the Vinces canton, its objective was to evaluate the development of language and its impact on reading and writing in children of Initial 1. The methodology used consists of a non-experimental design of cross-sectional, an explanatory, descriptive and documentary, survey technique and interview with their respective instruments, which were directed to an investigation of 35 infants and an initial teacher 1. The results were that the majority of students do not have a language According to their age, children are sometimes able to participate in short conversations, infants sometimes describe the images they see, parents consider language important for the development of children, the teacher uses different strategies such as reading, games, songs, among others. As conclusions, language development in preschool children plays a fundamental role for the acquisition of literacy skills. Language development in children has certain weaknesses such as difficulty describing images, writing clearly, repeating phrases or sentences. The literacy techniques used by the teacher consist of reading books, conversations, games, the use of songs and images, riddles and rhymes. As recommendations, that initial teachers carry out periodic evaluations to identify the abilities and weaknesses of each child in language development, use of visual and auditory resources most of the time.